A rare case of bilateral septic arthritis of hip: in a patient of idiopathic angiodema - Rafiq, Kanwal; Bhutta, Faisal Saeed (International Journal of Research in Medical Sciences, 2023)
Enterococcal infection can lead to gastroenteritis and bacteraemia. However, osteoarticular infections caused by Enterococci are rarely encountered. We report the case of a 27-year-old female patient with bilateral hip infection caused by enterococci. This young female patient initially presented with flare up of angioedema symptoms followed by septic arthritis of one hip and then 2nd hip while patient was admitted in hospital. Thankfully this patient was successfully treated and discharge back home. Early detection and proper treatment are essential for the eradication of the infection. The use of prolonged antimicrobial therapy can be considered in the management of bilateral hip joint destruction due to delayed diagnosis of enterococci infection. The patient was informed that data from the case would be submitted for publication, and she provided his consent.